2019
DOI: 10.3390/w12010062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bed Form Celerity on Oxygen Dynamics in the Hyporheic Zone

Abstract: Oxygen distribution and uptake in the hyporheic zone regulate various redox-sensitive reactions and influence habitat conditions. Despite the fact that fine-grain sediments in streams and rivers are commonly in motion, most studies on biogeochemistry have focused on stagnant sediments. In order to evaluate the effect of bed form celerity on oxygen dynamics and uptake in sandy beds, we conducted experiments in a recirculating indoor flume. Oxygen distribution in the bed was measured under various celerities usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…This Special Issue consists of 20 original research papers . The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue consists of 20 original research papers . The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
“…Ward et al [20] used the resazurin-resorufin reactive tracer system to study aerobic microbial transformation at sediment-water interfaces and found that the resazurin-to-resorufin transformation rate was highest in youngest storage locations (i.e., that increasing residence times do not necessarily increase the reaction potential of solutes). Wolke et al [21] systematically studied the impact of bed form movements on oxygen dynamics in the hyporheic zone. The advantage of such flume studies is the ability to conduct analyses under well-controlled environmental parameters.…”
Section: Hyporheic Zone Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrologic dynamism in rivers occurs over a wide range of timescales [ Boano, et al ., 2015, Kirchner and Neal , 2013, Woessner , 2000]. Increasing attention has been paid to the impact of short term hydraulic perturbations, on the hours-to-days scale, such as those created by hydropeaking, tidal forces, evapotranspiration, and other highly dynamic processes [ Singh, et al ., 2019, Wolke, et al ., 2020]. These intricately linked and highly dynamic processes combine to control the concentrations of chemical markers related to biogeochemistry in the riverbed, particularly electron donors and acceptors [ Stegen, et al ., 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Galloway et al (2019) evaluated oxygen dynamics under unsteady flow with various gaining and losing conditions and evaluated oxygen concentrations with the planar optode to calculate oxygenated areas. Likewise, Wolke et al (2020) quantify oxygenated areas to determine oxygen dynamics and consumption based on migrating bedforms (i.e., bedform celerity). While these studies have helped understand oxygen dynamics in the hyporheic zone, they do not analyze mixing‐dependent reactions.…”
Section: Introductionmentioning
confidence: 99%